Reconsidering concept of knowledge sharing: search for quality dimensions. Issue 5 (20th March 2020) - Doronin, Dmitrii; Lei, Shen; Shah, Syed Hamad Hassan
Abstract : Purpose: Importance of knowledge sharing is undeniable; however, a number of studies have shown it is not always beneficial. The purpose of this study is to breakdown existing definitions of knowledge sharing to understand what elements of it might be considered in quality dimension measures and based on those synthesize a more comprehensive definition. Design/methodology/approach: Through bibliometric investigation, the most influential definitions were investigated and the concept of knowledge sharing was redefined according to a process structure with the help of Grounded Theory. Findings: The research has revealed the dual nature of knowledge sharing, that is, knowledge as input and sharing as a process. Related quality measures were proposed. Originality/value: This study opens up a basis for future research of how companies and organization can improve the benefits of knowledge sharing by paying attention to its quality rather than quantity.